Programming fundamentals using Java : a game application approach - McAllister, William (William James); Fritz, Jane, Sister (Mercury Learning and Information, 2015)
Designed as a Java textbook for beginning programmers, this book uses game programming as a central pedagogical tool to improve student engagement, learning outcomes, and retention. It features: material that is in compliance with the forthcoming ACM/IEEE 2013 computer science curriculum guidelines; includes information on programming of mobile applications and several simulations that graphically depict unseen runtime processes such as the construction and destruction of objects, the passing of parameters, dynamic creation of an array of objects, polymorphic method invocations, and backtracking using recursion. --